MODERN TECHNOLOGIES IN THE PHARMACEUTICAL INDUSTRY - Kuvatov Jurʼatbek Dilshadbekovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In recent decades, the pharmaceutical industry has undergone a transformative journey, driven by the integration of modern technologies. These advancements have not only accelerated drug discovery and development but have also improved patient outcomes, personalized treatments, and overall operational efficiency. In this article, we will explore the various facets of modern technologies shaping the future of the pharmaceutical landscape.